Enhancing laminate composites: Investigating the impact of kevlar layering and titanium carbide nanoparticles - Oktaviani, Adinda; Zulfia, Anne; Rahmadiawan, Dieter (Universitas Negeri Padang, 2023)
The quest for innovative and superior materials is a challenge in the realm of materials science and engineering. Traditional materials often fall short in meeting the demands of modern industries, especially in the military. Technological developments in the military domain are still progressing, one of which involves a new material for combat vehicle applications: a laminated composite. In this research, a composite consisting of AA7075 sheet metal and kevlar with epoxy resin and TiC nanopowder were prepared. A test was conducted to assess its performance in absorbing ballistic energy from projectiles. Solid Thickening Fluid (STF) was created by mixing TiC nanopowder with PEG-400 through 2 hours of stirring. The laminate composite structure was prepared using the hand layup method, followed by a drying process at room temperature. The addition of kevlar layers yielded promising results in the ballistic and impact tests, as the diameter of the perforation decreased progressively with each additional kevlar layer. The IK sample impact test value improved by 35.7% compared to the unimpregnated one. The production process of this material also consumes minimal energy, which suggest a potential for environmental sustainability.